Efeitos da ingestão aguda de etanol em camundongos - Bruna de Paula Santos (2008)
Alcohol is the abuse substance more consumed all over the world. The direct effects of ethanol ingestion in the gastrointestinal tract includes morphological and functional disturbances such as cytotoxic injury, exfoliation epithelial cells and increased mucosal permeability that allows antigens access. Ethanol leads to immunological changes that favor Th2 responses and suppress Th1 responses. It induces secretion of inflammatory cytokines, and production of serum IgE even when consumed at moderate quantities. Ethanol is also a potent immunosuppressive drug, it modulates antigen-presenting cells (APCs), interferes with phagocytosis, and activation of immune responses increasing the risk of infection. In brief, ethanol induces alterations in both innate and acquired immunity.In this study, we observed that oral administration of ethanol during 4 consecutive days modulated the expression of molecules that are associated with antigen presentation in APC populations of spleen, mesenteric lymph nodes, peritoneal lavage fluid and peripheric lymph nodes of C57BL/6 mice. These changes were dependent on the type of molecule MHC-II, CD40, CD80, CD86, TLR2 or TLR4, the population of APC macrophages, dendritic cells or B cells, and organ analyzed. After 20 days, there were changes in the pattern of alterations observed right after ethanol ingestion. In C57BL/6 mice, ethanol-induced gastritis is characterized by increase in the levels of serum IgE, anemia and morphological changes in the stomach as well as in the proximal portion of small intestine such as epithelial dissociation, edema and presence of inflammatory infiltrate. One week later, we detected leucopenia and reduction of inflammatory events. TLR4-deficient C57BL6 mice were less susceptible to the local and systemic effects of ethanol. The morphological changes in the tract gastrointestinal were less severe than in wild type mice, and they were not detected one week later.Therefore, we concluded that TLR4 receptor is associated with acute gastritis and the systemic effects induced by oral ethanol administration and that the ingestion of this substance alters the expression of molecules that are related to antigen presentation by APCs.